Margarine and the origins and timing of microeconomic reform in Australia. (13th January 2015) - Abbott, Malcolm
Abstract : The production of margarine in Australia was for a long time the subject of strict quotas designed to limit the output of the industry in order to protect the dairy industry. The industry was effectively deregulated by the Whitlam, Dunstan (South Australia) and Wran (New South Wales) governments in the years 1975 and 1976. This move was effectively the first measure designed to deregulate an industry in modern Australian economic history and aimed to promote competition in order to improve efficiency and community welfare. It also began the long process of eliminating government intervention in the Australian dairy industry, which was not to be completed until 2000.